New Directions in the Sociology of Chronic and Disabling Conditions
XIII, 235 p.
Keywords: Bringing together disability theorists and medical sociologists for the first time in this cutting-edge collection, contributors examine chronic illness and disability, disability theory, doctor-patient encounters, lifeworld issues and the new genetics.